Cervical ganglioneuroma: a case report - Motter, Dema; Suseeharan, Melanie; Wahba, Basim; Hone, Robert (International Surgery Journal, 2022)
Cervical ganglioneuroma (CGN) is a rare benign tumour that originates from the neurogenic soft tissue of the cervical sympathetic chain. It is part of the neuroblastic tumours that arise from the neural crest cells of the central or peripheral nervous system. The clinical presentation can range from a palpable mass in the neck, dysphagia, dysphonia, or features of Horner’s syndrome. We present a case of a 65-year-old lady that was seen in the ENT outpatient clinic with complaints of left-sided neck swelling, dysphagia, and dysphonia. Complete surgical excision of the mass revealed the histological diagnosis of CGN. Treatment is considered complete when the entire specimen is excised.